Design and management of public health outreach using interoperable mobile multimedia: an analysis of a national winter weather preparedness campaign. (December 2016) - Bandera, Cesar
Abstract Background The Office of Public Health Preparedness and Response (OPHPR) in the Centers for Disease Control and Prevention conducts outreach for public preparedness for natural and manmade incidents. In 2011, OPHPR conducted a nationwide mobile public health (m-Health) campaign that pushed brief videos on preparing for severe winter weather onto cell phones, with the objective of evaluating the interoperability of multimedia m-Health outreach with diverse cell phones (including handsets without Internet capability), carriers, and user preferences. Methods Existing OPHPR outreach material on winter weather preparedness was converted into mobile-ready multimedia using mobile marketing best practices to improve audiovisual quality and relevance. Middleware complying with opt-in requirements was developed to push nine bi-weekly multimedia broadcasts onto subscribers' cell phones, and OPHPR promoted the campaign on its web site and to subscribers on its govdelivery.com notification platform. Multimedia, text, and voice messaging activity to/from the middleware was logged and analyzed. Results Adapting existing media into mobile video was straightforward using open source and commercial software, including web pages, PDF documents, and public service announcements. The middleware successfully delivered all outreach videos to all participants (a total of 504 videos) regardless of the participant's device. 54 % of videos were viewed on cell phones, 32 % on computers, and 14 % were retrieved by search engine web crawlers. 21 % of participating cell phones did not have Internet access, yet still received and displayed all videos. The time from media push to media viewing on cell phones was half that of push to viewing on computers. Conclusions Video delivered through multimedia messaging can be as interoperable as text messages, while providing much richer information. This may be the only multimedia mechanism available to outreach campaigns targeting vulnerable populations impacted by the digital divide. Anti-spam laws preserve the integrity of mobile messaging, but complicate campaign promotion. Person-to-person messages may boost enrollment.